Fungsi Dan Pengaruh Visi Misi Pada Sebuah Organisasi SD Negeri 02 Pulau Besar - Feyza Yudhistira; Aditiya Dwi Pangestu; Alif Akbar; Miftahul Hayatunnisa; Lusi Utari; Yoga Pratama; Indah Noviyanti (Pusat Riset dan Inovasi Nasional, 2023)
Vision and mission are statements that describe the goals and directions to be achieved by the school. The vision articulates the school's long-term goals, while the mission defines how the school will achieve this vision. These two elements are important in school development because they provide guidance, purpose, and focus for the entire school community. This study aims to investigate the influence and role of vision and mission in SD Negeri 2 Pulau Besar in achieving educational goals. Through qualitative research methods, including interviews, observation, and document analysis, this study aims to gain an in-depth understanding of how the vision and mission affect the school. In the context of SD Negeri 2 Pulau Besar, the school's vision and mission will play the role of accelerator and mover. An effective vision and mission can motivate and inspire the entire school community, including students, teachers and staff, to work towards the same goals. A clear and strong vision provides a view of what the school wants to achieve, while the mission sets out concrete strategies and steps to achieve this vision. Through this research, it is hoped that there will be a positive influence from the vision and mission of SD Negeri 2 Pulau Besar on the achievement of educational goals. This will provide important insights for education stakeholders, including teachers, principals and policy makers, in designing and implementing an effective vision and mission in schools. With a deep understanding of the impact of vision and mission, stakeholders can work together to create a learning environment that is motivating, focused and oriented towards achieving the desired educational goals. This research is also expected to contribute to further educational research on the role of vision and mission in the context of basic education. With a better understanding of the impact and function of vision and mission, other schools can adopt best practices that have proven effective and improve their efforts in achieving the educational goals set.